A convenção de Budapeste e a cooperação jurídica internacional como ferramentas essenciais na repressão aos crimes cibernéticos no Brasil - Silva, Matheus Giboski Moreira da (Universidade do Vale do Rio dos Sinos, 2021)
The technological advance opens up frontiers previously unexplored by human beings. In particular, the emergence of the internet has changed the way of life of society in general, whether professional or personal, creating almost a dependency on the tool. Ways of working and even contact with social circles are just examples of conveniences and facilities brought about by the internet. However, the use of this global instrument of instantaneous propagation and multitasking attracts the eyes of malicious people ready to take advantage of a complex system and, even though almost everyone uses it, few have the technical knowledge to protect themselves from these threats. Cybercrime is an extremely current reality and an urgent concern that States must have, inclusive because the governments themselves are also targets of cybercriminals. Therefore, as a way of repressing these criminal conducts that do not respect border barriers, unlike common crimes, countries around the world must adopt measures and cooperate with each other, facilitating the exchange of information, diplomatic rapprochement and avoiding conflicts of sovereignty, seeking an increasingly safe environment for internet users inside their respective countries. The Budapest Convention represents the main framework for international cooperation in the repression of cybercrime and, unfortunately, Brazil has not yet adhered to the treaty, although the measure is urgent in one of the countries that suffer most from cybercrime
Keywords: Crime cibernético; Convenção de Budapeste; Cooperação Jurídica Internacional; Cyber crime; Budapest Convention; International Judicial Cooperation